A representação da nasalização na escrita: uma proposta didática para o 2º ano do Ensino Fundamental - Nascimento, Emanuela Bravo do (2021)
This Master thesis reports a qualitative interpretivist research on the written representation of nasalization in Portuguese. The general aim was to present a didactic proposition for addressing the written representation of nasalization by students during the writing acquisition process. For achieving this goal, based on the forms of representing the nasal sounds in writing by students of the 2nd year of Elementary School of a municipal school in Cascavel (Paraná, Brazil), readings and reflections on themes related to literacy (writing acquisition), spelling and phonology were carried out, in order to support the development of the didactic material. The theoretical framework is based on studies carried out by authors such as Ferreiro (1992), Ferreiro and Teberosky (1999), Abaurre, Fiad and Mayrink-Sabinson (1997), Capistrano (2007) and Lemle (2009), among others, for the characterization of the writing acquisition process; Cagliari (1992, 2002) and Morais (2000, 2003), among others, for the reflections on the teaching of spelling; and Camara Jr. (1991), Battisti (1997), Ferreira and Correa (2010), Battisti and Vieira (2014) and Albertini (2017), among others, for the understanding of nasalization in Portuguese and its implications in the acquisition of writing. In relation to the data collected, the students’ records that deviated from the orthographic standard were classified based on the categories proposed by Ferreira and Correa (2010): a) omission of the nasalization marker; b) replacement of one nasalization marker by another; c) use of more than one nasalization marker; d) substitution unrelated to nasalization; e) changes in words. The analysis provided elements for the development of activities aimed at the systematic approach to the different nasalization markers, not only the ones related to the nasal or nasalized vowels, but also the nasal palatal consonant NH. It is expected that this research contributes to the teaching of Portuguese for the earlier grades regarding the appropriation of the standard orthography, with special attention to the representation of nasalization.